Survival Analysis of Child Patient Diarrhea Using Kaplan Meier Method and Rank Log Test - Muhammad Muhajir; Yayi Diyah Palupi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Diarrhea being one of public health problems that important because it is third major contributor theÂ pain children in various countries including indonesia. This research using data from islam hospital medical record jakarta in january 2017 shows that diarrhea cases were occupying the highest rank of various types of disease in patients children, using indicators long healed patients , the age of , andsex. Methods used to determine function survival who dominated in patients children are Kaplan Meier and Log Rank. The results of the analysis method kaplan meier got that patients male had the probability of healed longer than for patients female as well as patients age of 6- 11 years had the probability healed longer than the age of â‰¤ 5 years. To Log Rank test got that there is no significant difference between the survival function based on sex and age patients.